Effects of Seedling Raising Methods on the Economic Performance of Manually Operated Paddy Transplanter - Islam, Md. Syedul; Ahmad, Desa (Universiti Putra Malaysia Press, 2000)
A study was conducted to identify the effects of different seedling raising media on the economic performance of a manually operated transplanter. The costs of seedling production in wooden frame, bamboo frame, plastic frame, nylon rope and plastic tray nurseries for transplanting one hectare of land were US$27.21, US$27.77, US$27.20, US$27.04 and US$44.89 respectively. However, for wet bed nursery, it was only US 19.32. The net benefit from machine transplanting with wooden, bamboo and plastic frame seedlings were US$ 13.48, US$ 19.46 and US$ 16.05 per ha respectively compared to hand transplanting with wet bed seedlings. Among the five seedling raising media, plastic frame was considered the most appropriate one, where the break-even area per year is only 1.9 ha. Using this technique, a farmer can save about US$ 16.0 per ha compared to hand transplanting method.